Bridging the gap between formal and experience-based knowledge for context-aware laparoscopy - Katić, Darko; Schuck, Jürgen; Wekerle, Anna-Laura; Kenngott, Hannes Götz; Müller, Beat P.; Dillmann, Rüdiger; Speidel, Stefanie (International journal of computer assisted radiology and surgery, 2016)
Computer assistance is increasingly common in surgery. However, the amount of information is bound to overload processing abilities of surgeons. We propose methods to recognize the current phase of a surgery for context-aware information filtering. The purpose is to select the most suitable subset of information for surgical situations which require special assistance.
Gesehen am 07.05.2020